Capital city in the perceptions of "the best Lithuanian" - Vaicekauskienė, Loreta (Taikomoji kalbotyra, 2014)
The paper examines the ideology of the best language in the Lithuanian speech community. The research is based on synthesis of various metalinguistic data collected during previous research by the author. The regularity of the findings and stereotypical attitudes found in the data suggest that the idea of ​​the best Lithuanian in the Lithuanian speech community is closely linked to the largest city of Lithuania and the one of the highest social status – the capital Vilnius. Through the association with the city of Vilnius, the language of the „metropolis” and the „capital” acquires prestigious social meanings and the highest position in the hierarchy of Lithuanian language varieties. Metalinguistic localization in the metropolis gives following attributes to the best Lithuanian: non-dialectal, grammatical, correct, spoken by educated persons. Additional social values are developed through the association with the dwellers of the capital city and the urban center of the country itself: “modern”, “youthful”, “international”, “cosmopolitan”, “advanced”, as well as “self-confident”, “successful”, “wealthy”, “educated” and “cultivated”. All these attributions can be linked to the category dynamism, a valuable social value for, especially, young members of the community. Compared to the studies conducted elsewhere, it can be assumed that both linking of the ‘best speech’ with the speech of the metropolis or the capital city and the positive social associations of the capital city, is universal. All the research data collected using different methods during different investigations point to that there is basically no hierarchical relationship between the Vilnius speech and the standard Lithuanian in the best language perceptions of the Lithuanians. These two varieties are being integrated into one concept of the best speech spoken by best speaker, the one of the highest status, the most dynamic and competent as well possessing the best personality traits. Neither the stereotypical features associated with Vilnius speech (such as language mixing), nor the structural features of it (such as the so-called vowel lengthening, heavily criticized by the Lithuanian standard speech norm-setters), do not affect the concept of the best language by the community. Vilnius residents themselves and the general speech community evaluate linguistic features and prestige of the Vilnius speech differently from normative textbooks. The research presented in the paper makes it possible to predict that the link between capital Vilnius and the best speech of the community is the condition that will allow the speech of Vilnius to be taken over by language users and spread.